The effect on behavior and bone mineral density of individualized bone mineral density feedback and educational interventions in premenopausal women: a randomized controlled trial [NCT00273260] - De Wit Laura; Frendin Sue; Oldenburg Brian; Winzenberg Tania; Riley Malcolm; Jones Graeme (BMC, 2006)
Abstract Background Limited information is available on ways to influence osteoporosis risk in premenopausal women. This study tested four hypotheses regarding the effects of individualized bone density (BMD) feedback and different educational interventions on osteoporosis preventive behavior and BMD in pre-menopausal women, namely: that women are more likely to change calcium intake and physical activity if their BMD is low; that group education will be more efficacious at changing behavior than an information leaflet; that BMD feedback and group education have independent effects on behavior and BMD; and, that women who improve their physical activity or calcium intake will have a change in bone mass over 2 years that is better than those who do not alter their behavior. Methods We performed a 2-year randomized controlled trial of BMD feedback according to T-score and either an osteoporosis information leaflet or small group education in a population-based random sample of 470 healthy women aged 25-44 years (response rate 64%). Main outcome measures were dietary calcium intake, calcium supplement use, smoking behavior, physical activity, endurance fitness, lower limb strength and BMD. We used paired t-tests, one-way ANOVA and linear regression techniques for data analysis. Results Women who had feedback of low BMD had a greater increase in femoral neck BMD than those with normal BMD (1.6% p.a. vs. 0.7% p.a., p = 0.0001), but there was no difference in lumbar spine BMD change between these groups (0.1% p.a. vs. 0.08% p.a., p = 0.9). Both educational interventions had similar increases in femoral neck BMD (Leaflet = +1.0% p.a., Osteoporosis self-management course = + 1.3% p.a., p = 0.4). Femoral neck BMD change was only significantly associated with starting calcium supplements (1.3 % p.a, 95%CI +0.49, +2.17) and persistent self-reported change in physical activity levels (0.7% p.a., 95%CI +0.22, +1.22). Conclusion Individualized BMD feedback combined with a minimal educational intervention is effective at increasing hip but not spine bone density in premenopausal women. The changes in behavior through which this was mediated are potentially important in the prevention of other diseases, thus measuring BMD at a young age may have substantial public health benefits, particularly if these changes are sustained.